Acute and Sub-acute oral toxicity studies of Deedan-A Unani drug in Albino rats - Showkat A. Dar , Khalid Ghazanfar , Seema Akbar, Akbar Masood, Tazeen Nazir, Khalid M. Siddiqui, Pawan Kumar (Journal of Applied Pharmaceutical Science, 2015)
Deedan is a very effective compound formulation of Unani System of medicine used for the treatment of worm infestation. The objective of this study was to investigate the Acute and Sub-acute toxicity of Deedan in Albino rats of both the sexes. In the acute toxicity study, Deedan was administered orally at the limit dose of 2000mg/kg b.w. to both male and female rats, and the animals were then observed individually 30 minutes, 4 hour post-dosing, and at least twice daily for next 14 days. In the Sub-acute toxicity study a limit dose of 1000 mg/kg body weight was administered orally in a single bolus everyday for 28 days. The rats were observed daily during the period of study, and sacrificed on the 29th day. Observation parameters of the animals included a comparative evaluation of general appearance/behaviour, morbidity/mortality, body weights, food/water consumption, haematology, biochemistry and histopathology of major organs of treated and control groups. There was no mortality, morbidity, or cage-side/laboratory findings of any adverse health effect in the treated animals in comparison to their respective controls in both toxicity studies. Deedan was thus found to be free of any toxic effects under the conditions of these studies.
Keywords: Acute toxicity, subacute toxicity, Deedan, triglycerides, histopathology.